2017
DOI: 10.5056/jnm16027
|View full text |Cite
|
Sign up to set email alerts
|

Irritable Bowel Syndrome and Nickel Allergy: What Is the Role of the Low Nickel Diet?

Abstract: Background/AimsIrritable bowel syndrome (IBS) is characterized by chronic abdominal pain or discomfort accompanied by abnormal bowel movements. In sensitized subjects, ingested nickel (Ni) may induce gastrointestinal symptoms similar to IBS, in addition to typical systemic cutaneous lesions (systemic nickel allergy syndrome [SNAS]). A low nickel diet could improve the systemic manifestations. We evaluated prevalence of nickel allergy in IBS and effects of low Ni diet on (1) gastrointestinal symptoms control, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…In the present study, we have analyzed the effectiveness of the combination of a low-Ni diet with the supplementation of a specific probiotic, selected on the basis of the dysbiosis type. First of all, confirming what some groups have previously reported [5,8,10,11,13,41], we want to emphasize that the low-Ni diet was very effective in reducing the clinical symptoms associated with SNAS, resulting in a significant increase in skin and oral Ni-tolerance levels. The assessment of urinary marker levels of gut microbiota functional imbalance, i.e., indican and skatole, allowed us to identify the type of dysbiosis in the 51 patients with SNAS, thus helping to accurately prescribe the most appropriate probiotic formulation.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we have analyzed the effectiveness of the combination of a low-Ni diet with the supplementation of a specific probiotic, selected on the basis of the dysbiosis type. First of all, confirming what some groups have previously reported [5,8,10,11,13,41], we want to emphasize that the low-Ni diet was very effective in reducing the clinical symptoms associated with SNAS, resulting in a significant increase in skin and oral Ni-tolerance levels. The assessment of urinary marker levels of gut microbiota functional imbalance, i.e., indican and skatole, allowed us to identify the type of dysbiosis in the 51 patients with SNAS, thus helping to accurately prescribe the most appropriate probiotic formulation.…”
Section: Discussionsupporting
confidence: 88%
“…Replacement of dental alloys with non-metal materials, as well as dietary control of nickel and palladium intake, may thus enhance the therapeutic effect of existing pharmacotherapy for UC patients. In this context, it is interesting to note that a low-nickel diet clearly alleviates the gastrointestinal symptoms of patients with irritable bowel syndrome [28], a disease that involves low-grade mucosal inflammation and aberrant T-cell activation similar to those in UC [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to dietary nickel has been recently proposed as a cause of IBS symptoms. In a clinical study, IBS patients with a positive nickel patch test were found to respond well to a low nickel diet with significant reductions in gastrointestinal symptoms [110]. It was hypothesized by the study investigators that dietary nickel may contribute to IBS symptoms by inducing a pro-inflammatory state.…”
Section: Nickel-related Intestinal Mucositismentioning
confidence: 99%
“…Diagnosis of dietary nickel sensitivity can be performed with a skin or oral mucosa patch test [110,112]. All patients reporting to a gastroenterology unit with IBS symptoms and suspected sensitivity to nickel containing foods had a positive response to an oral mucosa patch test characterized by local hyperemia and/or edema, compared to no response in a control group [113].…”
Section: Nickel-related Intestinal Mucositismentioning
confidence: 99%